Mirrors and Windows - Ismail Serageldin (International Institute of Islamic Thought, 1994)
On Boundaries Fmntiets are an invention of the mind. We set boundaries for ourselves and others by what we choose to see as reality and by what we choose to value. But men and women are social creatures, and individual behavior is subjected to the control of widely shared social values. These boundaries that define the limits of acceptable behavior also tend to reflect and reinforce limits on acceptable thinking. How are such social values developed? How do they change over time? The intelligentsiaartists and intellectuals-create mirrors through which we see outselves and windows through which we perceive reality. It is these mims and windows that define the boundaries of the mind. The intelligentsia's roleboth as makets of a cultual outlook and product of the milieu-is central to my view of what is happening in the world generally and in the Muslim societies of the Middle East particularly. These important questions will appear throughout this essay like a leitmotif. The intelligentsia needs a space offreedom in which it can perform its dual tole and shape the boundaries by which we define ourselves. Are such boundaries important? They cettainly are. Shared values reflected in predictable behavior not only are the basis of all social organization but are at the core of "cultural identity"a hackneyed expression that nevertheless remains essential to anyone who lives in a group.' Yet individuals within a group are not clones, interchangeable units within a collectivity. Each petson interacts with others in an expanding series of circles starting with high intensity vis-his the immediate family circle and with decreasing intensity to the limit of the group(s) with which the individual identifies ...